Determining the correlation between quality of life and self-concept in children with attention deficit/hyperactivity disorder - (:unkn) unknown (WILEY, 2014)
This study was conducted to determine the relationship between how children with attention deficit/hyperactivity disorder (ADHD) perceive their quality of life and their self-concept. The study involved descriptive/correlational research with 70 children, ages 9-12 with ADHD. Data were collected with the ADHD Quality of Life Scale (ADHD/QoLS) and the Piers-Harris Children's Self-Concept Scale (PHCSCS). Data were assessed using Pearson's and Spearman's correlation analysis; the level of significance was accepted as P < 0.05. The analysis of the data determined that there was a significant relationship between all of the domains of the Self-Concept Scale and ADHB/QoLS and its subscales (P < 0.001). An evaluation of the correlation analysis for the relationship between ADHD/QoLS and PHCSCS and their subscales revealed that there was a strong, positive and very significant relationship between ADHD and self-concept, both at school and at home.
Keywords: child and adolescent; cognitive and behavioural psychotherapy; nursing diagnosis; DEFICIT-HYPERACTIVITY-DISORDER; ESTEEM; ADHD; EDUCATION; IMPACT